Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor

Multi-dimensional impact of captopril modification on human serum albumin - Ghosh, Amrita; Jani, Vinod; Sonavane, Uddhavesh; Naphade, Anvi N.; Joshi, Rajendra; Kulkarni, Mahesh J.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2024)
Captopril is a thiol drug, widely used for the management of hypertension and cardiovascular diseases. Reactive thiols are found to covalently modify the cysteines of plasma proteins and affect their structure and function. Human serum albumin (HSA) is prone to undergo modification by various low molecular weight compounds, including drugs. Cysteine34 (Cys34) in HSA has a free thiol group with antioxidant properties, considered to be the most redox-sensitive amino acid in plasma. Through mass-spectrometric analysis, we demonstrate for the first time that captopril forms a disulfide adduct at Cys34 residue and increases the protease susceptibility of HSA to trypsin. As evidenced by our biophysical and electron microscopy studies, HSA undergoes structural alteration, aggregation and morphological changes when treated with different captopril concentrations. Molecular dynamics studies further revealed the regions of secondary structural changes in HSA due to disulfide adduct formation by captopril at Cys34. It also elucidated the residues involved in the noncovalent interactions with captopril. It is envisaged that structural change in HSA may influence the efficacy of drug delivery as well as its own biological function. These findings may thus provide significant insights into the field of pharmacology intriguing further investigation into the effects of long-term captopril treatment.
Keywords: Captopril; Electron microscopy; Human serum albumin; Mass spectrometry; Molecular dynamic simulation; Spectrophotometry

Unique microswitches positioned extracellular to the orthosteric binding site initiate activation in the β1-adrenergic receptor - Koulgi, Shruti; Harman, Thomas H.; Jones, Andrew J. Y.; Sonavane, Uddhavesh; Nietlispach, Daniel; Sengupta, Durba; Joshi, Manali (Journal of Chemical Information and Modeling, 2026)
Class A GPCRs are known to bind an astonishingly diverse set of agonists, ranging from ions and small molecules to peptides and large proteins that activate these receptors. Interestingly, despite this diversity, agonist binding is described to trigger a conserved activation pathway that propagates changes from beneath the orthosteric agonist-binding site toward the intracellular G protein-coupling site. This suggests the presence of receptor-specific residues upstream of the orthosteric agonist-binding site that not only enable recognition of the ligand but also trigger the common activation mechanism. Using the prototypical beta 1AR-G protein system, we employed microsecond time-scale atomistic molecular dynamics simulations together with NMR experiments to investigate how receptor-specific residues, in conjunction with agonist binding, initiate the conserved activation pathway. We identified state-dependent electrostatic and hydrophobic switches involving unique beta 1AR residues located above the orthosteric binding site, potentially linking them to receptor activation. Our simulations recapitulated the known common activation pathway and also uncovered beta 1AR-specific novel contacts. Additionally, we identified a unique water-mediated R-Y-Y switch near the intracellular end that could facilitate G protein coupling. Overall, based on our work, we propose how evolutionary variations in the extended ligand-binding site could enable receptor-specific agonist recognition, triggering and converging on the common activation mechanism and preserving G protein coupling fidelity.